Conceptions of Islam in Indonesian Public Life: a Study of The Nahdlatul Ulama’s Journal Tashwirul Afkar (1997-2016) - Vinken Geovannissa Wijaya (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
This research aims to show Nahdlatul Ulama's views regarding the proper role of Islam in Indonesian public life. The views of Nahdlatul Ulama are represented in a journal published by Nahdlatul Ulama, namely Tashwirul Afkar. This research will explore the discussion in the journal Tashwirul Afkar by focusing on three areas: history, intellectualism and sharia. h These three areas have been chosen because they reflect NU's views regarding the proper role of Islam in Indonesian public life. The relationship between Islam and the state is conceptualized by differentiating Islamic values and formalities. In the life of an Islamic state, it is used as an inspiration, not as a state aspiration, so NU describes it as a state based on Islamic values, not Islamic formalities. NU's reluctance to apply the formalities of Islamic law (shariah) has a fiqh basis, so even though NU supports state law, NU will accept national law as long as it does not conflict with sharia law. In short, the journal Tashwirul Afkar has articulated a set of viewpoints from within NU on the proper role of Islam in Indonesian public life. This research seeks to add to our understanding of the diversity of voices and aspirations within Nahdlatul Ulama in Indonesia today.